Somatotypic changes in eryptorhismie boys - Malinowski, Andrzej (Anthropological Review, 1982)
During 1976 and 1977 were carried examinations of 96 boys aged 3-16 years in whom were found bilateral (30 subjects) and unilateral (41 subjects) lack of testicles in the scrotum or their dislocation — ectopy (25 subjects). All subjects were measured with use of standard anthopometric techniques, individual measurements were standarized, with respect to age of a subject, on data pertaining to normal children from the same city (Poznan) constituting a developmental norm. Deviation of somatotypes from that norm was analysed in three groups of subjects separately: 1. neutral childhood (3 -10 yrs), 2. prepubertal (11-12 yrs) and 3. pubertal (13 -16 yrs). The largest deviations from the norm were found in the third group, the smallest in the first one (fig. 2). The strongest abnormalities in physique were observed in boys with bilateral lack of testicles at their normal position, the smallest — in ectopic subjects (fig. 3). Somatotypic changes of cryptorhismic boys concern mainly body proportions being expressed in narrowing of shoulders, broadening of hips, shortening of the trunk and elongation of lower extremities (so called ,,eunuchoid physique”).